Development of an intuitive foot-machine interface for robotic surgery - Huang, Yanpei (Nanyang Technological University, 2021)
In robotic surgery, the surgeon controls the surgical robot through human-machine interfaces. The most common interfaces are for hands so that the surgeon can only control at most two robotic instruments at one time while three or more instruments may be needed at the same time in some procedures, e.g., robotic endoscopic/laparoscopic surgery. Current practices in these cases, i.e., having one assistant control the additional instrument, is not ideal because fine collaboration between the surgeon and the assistant is required, and delayed actions and even safety issues due to communication errors may occur. These limitations can be avoided if the surgeon could control all the tools on his/her own simultaneously. This thesis work developed a novel foot-controlled human-machine interface, enabling the surgeon to control the additional robotic surgical tool using the foot, together with the two tools that are controlled by the hands.